New species of Hydroptilidae (Trichoptera) from Salto Encantado Provincial Park (Misiones province, Argentina) - Angrisano, Elisa B.; Sganga, Julieta V. (Zootaxa, 2009)
Seven new species of Hydroptilidae from Misiones province are described, Alisotrichia cainguas new species, Metrichia pitu new species, Ochrotrichia pora new species, Paratrichia acuti new species, Rhyacopsyche garuape new species, Oxyethira tamandua new species, and Oxyethira poapi new species. The genera Ochrotrichia Mosely and Paratrichia Angrisano are recorded for the first time from Argentina.